Women footwears of Choice: A Correlation Analysis of Customer Attitudes toward Purchase Intention of Local Footwear Products - Dewi Nursilowati , Rani; Mayangsari, Lidia (KnE Social Sciences, 2020)
There are differences between the preference of women and men as consumers. Women are more emotionally unstable, and open to feelings and aesthetic experiences. In this intense competition between local and imported footwear which is global brands, it is challenging for local footwear products to survive in the industry. It is a requirement for the brands (in this research, local footwear brands) to understand the attitudes of the customers from time to time, especially women. Hence, the marketer needs to understand the factors influencing customer purchase intention for local footwear products. This research is a quantitative research that conducted to explore the objective of the study. The method used is surveying by questioning the respondents to gather information. The researcher has conducted the survey through an online questionnaire as a tool for data collection with the total of 242 respondents. The population of this study is consisted of women between age 15-54 years old that have ever been buying local footwear products. In this study, as part of convenience sampling, we select non-probability sampling which is a judgmental sampling. Then, the data are analyzed using validity, reliability, classical assumption, pearson, simple linear regression, and descriptive analysis. After the analysis sequence has been performed, the formulated comprehensive description of findings are presented. Keywords: women, local footwear product, customer attitude, purchase intention